How I do it: modification of the posterior pedicled nasoseptal flap for clival and nasopharyngeal surgery - Campbell, Raewyn G.; Otto, Bradley A.; Prevedello, Daniel M.; Carrau, Ricardo L. (Australian Journal of Otolaryngology; Vol 1 (March 2018): Australian Journal of Otolaryngology, 2018)
The posterior pedicle nasoseptal flap, also named the Hadad-Bassagaisteguy flap, was developed at the University of Rosario, Argentina by Hadad and Bassagaisteguy, and modified by Carrau with the aim to design a better intranasal vascular pedicled flap for skull base reconstruction (1,2). The posterior pedicle nasoseptal flap provides an ample surface area with a superior arc of rotation and is therefore a reliable flap, especially for the reconstruction of large skull base defects.